Cardiotoxicity associated with oncological chemotherapy: Identification of risk factors - Silva, Paloma Geralda Mizael de Paula (2021)
Objective: To identify the risk factors for cardiotoxicity in cancer patients undergoing antineoplastic treatment. Methodology: Integrative literature review, performed in the MEDLINE/PUBMED, SCIELO AND VHL databases, by crossing the descriptors: neoplasms, clinical protocols, risk factors and cardiotoxicity and their respective interconnected terms by the Boolean operators “AND” and “OR”, with a time frame from 2017 to 2019). Results: After reading and analyzing the works (n: 30) found, seven categories emerged: Overweight and obesity; cardiac arrhythmias; preexisting disease, mediastinal irradiation, genetic predisposition; physical inactivity; systolic arterial hypertension, diabetes, dyslipidemia and smoking; long therapy time and cumulative dose; association of chemotherapy classes. Conclusion: Many risk factors are present in cancer patients, thus contributing to the development of cardiotoxicity. Accordingly, it is essential that oncological nursing has, in its practice, focus on early identification of them, in order to prevent and control cardiotoxicity.